Angiotensin Converting Enzyme Inhibitors Combined with Exercise for Hypertensive Seniors (The ACES Trial): Study Protocol of a Randomized Controlled Trial - Harper, Sara A.; Baptista, Liliana C.; Roberts, Lisa M.; Wherry, Sarah J.; Boxer, Rebecca S.; Hildreth, Kerry L.; Seay, Regina S.; Allman, P. Hunter; Carter, Christy S.; Aban, Inmaculada; Kohrt, Wendy M.; Buford, Thomas W. (Frontiers in Medicine, 2020)
Prior evidence suggests that the choice of antihypertensive medication may influence functional status among older adults with hypertension, particularly in conjunction with exercise. In particular, angiotensin converting enzyme (ACE) inhibitors have shown potential to positively influence function. However, randomized, controlled trials are needed to confirm this hypothesis. This paper outlines an RCT designed to determine if choice of first-line antihypertensive medication influences functional and cardiovascular risk factor responses to exercise among older adults with hypertension. Two hundred thirteen inactive, community-dwelling adults ≥ 60 years of age with hypertension and functional limitations will be recruited to engage in a 32-week intervention study. Participants will be randomized to one of three first-line antihypertensive agents: (1) the ACE inhibitor perindopril, (2) the AT1 receptor antagonist losartan, or (3) the thiazide diuretic hydrochlorothiazide (HCTZ). Six weeks after randomization, participants will begin a 20-week structured aerobic exercise intervention. Participants will perform two 45-minute center-based sessions coupled with 60 minutes of home-based walking per week. The primary aim is to determine if perindopril improves self-paced gait speed when compared with losartan and HCTZ. The secondary aim is to determine the relative effect of perindopril on secondary outcomes such as: a) exercise capacity, b) body mass and composition, and c) circulating indices of cardiovascular risk. This RCT is expected to identify differential effects of first-line antihypertensive medications when combined with physical exercise thus have potential implications for antihypertensive prescription guidelines for older adults.